Investigating the simple and multiple relationship between critical thinking and learning styles and creativity among high school students in Ahvaz - Abbas Rohani (Shahid Beheshti University of Medical Sciences, 2023)
Background: Creativity is a person's ability to create ideas and insights in science and other fields, learning critical thinking includes the development of thought processes beyond self-centered attitudes and perceptions and immediate sensory experience. This study aim was to investigate the simple and multiple relationships between critical thinking and learning style and creativity in Ahvaz high school students. Methods: All high school students in District 2 of Ahvaz (2000 people), who were studying in the academic year of 2018-2019 were included in the study. 280 of whom were selected as a sample by multi-stage random sampling. Data collection tools was included Abedi, Creativity Test, the California Critical Thinking Test and the Kolb, Learning Styles Questionnaire. To analyze data, Pearson correlation coefficient and multiple regression analysis were used. Results: There was a significant relationship between critical thinking, reflective observation and active experimentation and creativity. However, there was no significant relationship between concrete experience and abstract conceptualization and creativity in the subjects. Also, based on the results of regression analysis, among the predictor variables, critical thinking and reflective observation, respectively, were the best predictors for students' creativity. Conclusion: It seems that the educational and lesson planning of students should be reviewed and teachers should revise their teaching methods and use active teaching methods to encourage them to critical learning styles in students and promote creativity.